2020
DOI: 10.1039/d0dt00324g
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, chemical bonding, and electrical and thermal transport in Sc5Rh6Sn18

Abstract: Single crystals of Sc 5 Rh 6 Sn 18 were grown from Sn-flux. The crystal structure (SG: I4 1 /acd, a = 13.5529(2) Å, c = 27.0976(7) Å) was studied by high-resolution X-ray diffraction on powder and single crystal material as well as by TEM. All methods confirm it to crystallize with Sc 5 Ir 6 Sn 18 (space group I4 1 /acd) type of structure. The performed structural studies suggest also the presence of local domains with broken average translational symmetry. Analysis of the chemical bonding situation reveal hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 45 publications
7
17
0
Order By: Relevance
“…The synthesis and complete structural characterization of the octahedral crystals with a base of about 1 × 1 cm 2 and a height of about 1 cm (see Fig. 1 in [24]), on which the here-reported properties were measured, as well as the electronic structure and chemical bonding of Sc 5 Rh 6 Sn 18 are discussed in Ref. [24].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The synthesis and complete structural characterization of the octahedral crystals with a base of about 1 × 1 cm 2 and a height of about 1 cm (see Fig. 1 in [24]), on which the here-reported properties were measured, as well as the electronic structure and chemical bonding of Sc 5 Rh 6 Sn 18 are discussed in Ref. [24].…”
Section: Methodsmentioning
confidence: 99%
“…1 in [24]), on which the here-reported properties were measured, as well as the electronic structure and chemical bonding of Sc 5 Rh 6 Sn 18 are discussed in Ref. [24]. The performed diffraction studies showed Sc 5 Rh 6 Sn 18 [space group: I4 1 /acd, a = 13.5529(2) Å, c = 27.0976(7) Å] crystallizes with the Sc 5 Ir 6 Sn 18 type of structure [22].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations